Moral Leadership Using The Method Of Francis De Sales (The Macau Ricci Institute Journal, 2017)
Moral Leadership implies that the exercise of leadership should be carried out according to identifiable moral values. The exercise of responsible leadership can be an instance of moralleadership. Th is includes the identifi cation of stakeholders, and the provision of opportunity for stakeholders to participate in the ongoing processes of the organisation. Francis De Sales,who was lawyer, religious leader and founder of a religious order, writer and mentor, offers a practice or method which can be used for working with stakeholders. Although apparently simple, this practice is complex and rich with possibilities. De Sales introduces his practice in the context of buying and selling, but it can be extended for use in more complex transactions. This paper introduces the practice, here called “exchanging places”, explains how it functions, and notes somelimitations.